2012
DOI: 10.1002/jtr.1895
|View full text |Cite
|
Sign up to set email alerts
|

Distributed Fascinating Knowledge Over an Online Travel Community

Abstract: The research goal of this study was to investigate how website design quality and website service quality affect participation behavior in the online travel community by moderating tacit knowledge and commitment. The design of the questionnaire linked it to the invitation message on the three travel communities, of which 235 were returned completed. The finding of the study shows that an online travel community that allows quick manipulation capabilities is likely to attract its members. To succeed, online tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(11 citation statements)
references
References 61 publications
0
11
0
Order By: Relevance
“…In the context of e-service, there is little or no inter-personal interaction, and all the service encounters are information technology mediated (Curran & Meuter, 2005;Meuter, Ostrom, Roundtree, & Bitner, 2000), hence customer evaluation of the information technology's performance should be the main motivation to review generation in online communities. The two key constructs of perceived ease of use and perceived usefulness in the Technology Acceptance Model or TAM (Davis, 1989) are used to examine e-service experience (Ahn, Ryu, & Han, 2007;Ku, 2014;Li & Liu, 2014;Papadopoulos et al, 2013). Ahn et al (2007) examine customer e-retailing service experience by incorporating perceived ease of use and usefulness in their research model.…”
Section: E-service Experience and Knowledge Sharingmentioning
confidence: 99%
See 1 more Smart Citation
“…In the context of e-service, there is little or no inter-personal interaction, and all the service encounters are information technology mediated (Curran & Meuter, 2005;Meuter, Ostrom, Roundtree, & Bitner, 2000), hence customer evaluation of the information technology's performance should be the main motivation to review generation in online communities. The two key constructs of perceived ease of use and perceived usefulness in the Technology Acceptance Model or TAM (Davis, 1989) are used to examine e-service experience (Ahn, Ryu, & Han, 2007;Ku, 2014;Li & Liu, 2014;Papadopoulos et al, 2013). Ahn et al (2007) examine customer e-retailing service experience by incorporating perceived ease of use and usefulness in their research model.…”
Section: E-service Experience and Knowledge Sharingmentioning
confidence: 99%
“…Papadopoulos et al (2013) indicate that perceived usefulness and perceived ease of use of web-blog did not have a significant effect on knowledge sharing. In contrast, Ku (2014) builds upon TAM to examine website design and service quality and found positive impacts of traveler knowledge sharing in online communities. Li and Liu (2014) report perceived usefulness of e-service have a positive effect on word-of-mouth.…”
Section: E-service Experience and Knowledge Sharingmentioning
confidence: 99%
“…SI theory has been used in studies in the fields of tourism and technology (Casaló et al, 2010;Ku, 2012). Prior research has used SI theory to explain how a person identifies with others (Akkinen, 2005).…”
Section: Si Theorymentioning
confidence: 99%
“…Cognitive, affective, and evaluative components of customer brand identification interact with each other in realizing positive and negative eWOM (So, Wu, Xiong, & King, 2017;Su et al, 2014). Ku (2014) shed light on the dynamics within online travel communities and explored factors such as social identification that affect the sharing of tacit knowledge. Nusair, Bilgihan, and Okumus (2013) found that Gen Y travelers' use of social media is driven by innovativeness, desire to share information, and perceived utility, while their interactions are predictors of trust and loyalty.…”
Section: Online and Social Media Researchmentioning
confidence: 99%